Bullying and Ciberbullying “Post-Pandemic”: A Study with Schooled Adolescents in the City of Córdoba (Revista de Psicología, 2024)
Bullying and ciberbullying behaviors increased during the COVID-19 pandemic increased because of social isolation. The objective of this study was to build an explanatory model for bullying behaviors among peers in adolescents attending school in the city of Cordoba. A test battery was administered to 745 adolescents between 12 and 19 years old during the year 2022. A correlation analysis and a structural equation model were carried out. The results demonstrate an overlap between the different roles and an interrelation between individual and social variables. The role of the family and school climate as protective factors for involvement in these behaviors and the importance of the role of observer in its maintenance is highlighted.
Keywords: adolescence; bullying; cyberbullying; context; individual factors